The Relationship Between Physiotherapy Therapeutic Communication And Parents' Self-Efficacy In Implementing Home Programs For Children With Special Needs At The Special Children's Center Clinic In Medan - Nuri Putri Ayu; Leandra Erdina Usmani; Jhon Roby Purba; Enny Selawaty Boangmanalu (International Journal of Health Engineering and Technology, 2026)
The success of home programs for children with special needs is greatly influenced by the active involvement of parents. One factor thought to play a role in increasing parental self-efficacy is therapeutic communication conducted by physiotherapists during the rehabilitation process. Effective therapeutic communication can improve parents' understanding, motivation, and confidence in carrying out exercises independently at home. This study aims to analyze the relationship between physiotherapy therapeutic communication and parental self-efficacy in implementing home programs for children with special needs at the Special Children's Center Clinic. This study used an observational, analytical quantitative design with a cross-sectional approach. The study sample consisted of 22 parents of children with special needs selected using a total sampling technique. Data collection was conducted using the Physiotherapy Therapeutic Communication Instrument and the Home Program Self-Efficacy Questionnaire. Data analysis included univariate analysis, the Shapiro–Wilk normality test, and the Spearman Rank correlation test with a significance level of p<0.05. The results of this study showed that most respondents rated physiotherapy therapeutic communication as good (81.8%) and had a high level of self-efficacy (68.2%). The Spearman Rank correlation test showed a significant positive relationship between physiotherapy therapeutic communication and parental self-efficacy in implementing home programs (rₛ = 0.432; p = 0.045). This study concluded that there was a significant positive relationship between physiotherapy therapeutic communication and parental self-efficacy in implementing home programs for children with special needs. Improving the quality of physiotherapy therapeutic communication has the potential to increase parental confidence in carrying out exercises at home, thus supporting the success of child rehabilitation.